(untitled) (Cuadernos de antropología social, 2012)
Evaluadores extranjeros Alicia Barabas – Instituto Nacional de Antropología e Historia de México, México Martinho Braga Batista e Silva – Universidade do Estado do Rio de Janeiro, Brasil Josep Comelles – Universitat Rovira i Virgili, España Maria Leticia Mazzucchi Ferreira – Universidade Federal de Pelotas, Brasil Tomas Martínez Saldaña – Colegio de Postgraduados, México Gladys Nieto Martinez – Universidad Autónoma de Madrid, España Diana Reartes – Centro de Investigaciones y Estúdios Superiores en Antropología Social, México Cynthia Sarti – Universidade Federal de São Pablo, Brasil Daniel Schroeter Simião – Universidade de Brasília, Brasil Fernando Villaamil – Universidad Complutense de Madrid, España Adriana Maria Villalón González – Ankulegi, Asociación Vasca de Antropología, España José Manuel Zavala – Universidad Católica de Temuco, Chile Evaluadores nacionales Mirta Bialogorski – CONICET / Universidad de Buenos Aires Beatriz Goldwaser – Universidad Nacional de Luján Julieta Quiróz – CONICET / Universidad de Buenos Aires Héctor Vázquez – CONICET / Universidad Nacional de Rosario Ilustración de tapa Noticias de América, 2011, acrílico 180 x 200cm. Jesús Marcos, Artista Plástico